Corporate Environmental, Social and Governance Performance and Carbon Washing in China - Qingchao Zeng; Nuo Xu (Universitas Pasundan, 2024)
By focusing on a specific type of greenwashing behavior concerning carbon emission reductions, (i.e., carbon washing), the aim of this study is to investigate its antecedents in ESG (Environmental, Social and Governance) performance and find relevant solutions in Chinese context. This study is designed under a framework of greenwashing triangle for both analysis and examination. The measurement of carbon washing is based on text analysis and content analysis of non-financial reports, and the results are obtained by ordinary least squares regression. The results show a negative relationship between firms’ ESG performance and carbon washing tendency, which is mediated through lowering the standardization of carbon disclosure. To combat it, reducing opportunities and rationalizations are both effective avenues, while reducing pressure leads to complicated results. The results offer enlightenment for the cautious usage and regulation of firms’ carbon disclosures. Understanding the causes of carbon washing helps to distinguish good performers from poor performers concerning carbon reductions, hence increasing market efficiency. Finding relevant solutions helps to fight carbon washing acts and improve the quality of carbon information. The value of the study is offering new insights in the mis informativeness of carbon disclosure, which helps avoid the generalities in conventional discussions of greenwashing. The measurement of carbon washing is original, based on previous researches.